Epidemiology of Thyroid Cancer: Incidence and Mortality in China, 2015 - Du, Lingbin; Zhao, Zixuan; Zheng, Rongshou; Li, Huizhang; Zhang, Siwei; Li, Runhua; Wei, Wenqiang; He, Jie (Frontiers in Oncology, 2020)
Objective: Using data from cancer registries to estimate thyroid cancer incidence and mortality in China, 2015. Methods: Data submitted from local cancer registries were checked and evaluated according to the criteria of data quality control, a total of 368 cancer registries’ data were qualified for the final analysis. Data were stratified by area (urban/rural, eastern/central/western), sex and age, combined with national population data to estimate thyroid cancer incidence and mortality in China, 2015. Results: Approximately 200,700 new cases were diagnosed in 2015, accounting for 5.11% of all cancer cases. The crude incidence rate was 14.60/100,000. Age-standardized incidence rates by Chinese standard population (ASIRC) and world standard population (ASIRW) were 12.05/100,000 and 10.44/100,000, with the cumulative incidence rate (0−74 years old) of 1.00%. About 7,900 deaths of thyroid cancer were reported in 2015, accounting for 0.34% of all cancer deaths. The crude mortality rate was 0.58/100,000, age-standardized mortality rates by Chinese standard population (ASMRC) and world standard population (ASMRW) were 0.37/100,000 and 0.36/100,000. The age-standardized incidence and mortality in males were higher than those in females. The rates in urban areas were higher than those in rural areas. The ASIRC in eastern areas was higher than that in central and western areas, while the ASMRC in central areas was higher than that in eastern and western areas. Conclusions: The burden of thyroid cancer was heavy in China, cancer control faces the problem of the disparity between geographic area, age and sex. Targeted cancer preventive measures should be put into practice.